Evaluasi Pengelolaan Obat pada Tahap Perencanaan, Pengadaan, Penyimpanan dan Pendistribusian di Puskesmas X Kampar, Riau - Pratiwi, Denia; Adetian, Vini (Jurnal Farmasi & Sains Indonesia, 2024)
The importance of a series of drug management in a health care system cannot be ignored, because if it is not done efficiently, it will have a negative impact on the health centre both in medical, social and economic terms. This study was conducted to determine the suitability of drug management related to the processes of planning, procurement, storage and distribution of drugs at the Puskesmas X Kampar with the Pharmaceutical Service Standards (PSS) 2019. This study uses a type of qualitative research using interview techniques, observation and completion of checklist sheets. The data from the checklist sheet, observation sheet and interview guidelines were processed and analysed using the content analysis method. The results showed that Puskesmas X Kampar in planning was not in accordance with the Pharmaceutical Service Standards (PSS) 2019, in drug procurement and distribution Puskesmas X Kampar was in accordance with the PSS at Puskesmas. For storage, there were still some that were not in accordance with the PSS 2019 such as not having pallets, high alert drugs were not specially marked, flammable materials such as pharmaceutical preparations and consumable medical materials (CMM) were not stored in a separate place from other drugs and the refrigerator was in a damaged.